2013
DOI: 10.1186/1471-2148-13-81
|View full text |Cite
|
Sign up to set email alerts
|

Rapid adaptation to mammalian sociality via sexually selected traits

Abstract: BackgroundLaboratory studies show that the components of sexual selection (e.g., mate choice and intrasexual competition) can profoundly affect the development and fitness of offspring. Less is known, however, about the total effects of sexual selection on offspring in normal social conditions. Complex social networks, such as dominance hierarchies, regulate the opportunity for mating success, and are often missing from laboratory studies. Social selection is an extended view of sexual selection that incorpora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 59 publications
(93 reference statements)
1
19
0
Order By: Relevance
“…E-mail: adamnelson@fas.harvard.edu. revealed female mating and odor preferences for promiscuousline males (14). These results suggested that returning mice to sociality favored an attractive male-specific phenotype characterized by enhanced pheromone signaling, but conspicuously lacking in vigor and viability, a result consistent with the sexy sons hypothesis of sexual selection (14).…”
mentioning
confidence: 54%
See 3 more Smart Citations
“…E-mail: adamnelson@fas.harvard.edu. revealed female mating and odor preferences for promiscuousline males (14). These results suggested that returning mice to sociality favored an attractive male-specific phenotype characterized by enhanced pheromone signaling, but conspicuously lacking in vigor and viability, a result consistent with the sexy sons hypothesis of sexual selection (14).…”
mentioning
confidence: 54%
“…Adult "parents" experienced one of two treatments for roughly 8 wk: competition (C) or noncompetition (NC). Using the same protocol to generate promiscuousline and monogamous-line mice (14), C males and females were introduced to enclosures where they competed for resources, mates, and social dominance (12,14) whereas NC males and females experienced 8 wk in monogamous breeding cages. Following a brief intermission period (during which pups from pregnant females were removed), females and males were assigned, respectively, to monogamous breeding in the following four-way reciprocal breeding design: C 脳 C; C 脳 NC; NC 脳 C; and NC 脳 NC.…”
Section: Social Competition Triggers Maternal and Paternal Effects Onmentioning
confidence: 99%
See 2 more Smart Citations
“…Within these enclosures some, but not all, pressures of natural selection (e.g., predation) are absent, and most sexual selection pressures are present (including male鈥搈ale competition and female choice ((Meagher, Penn, & Potts, 2000; Nelson, Colson, Harmon, & Potts, 2013))). Therefore, by assessing the reproductive success of mice in semi鈥恘atural enclosures, one can evaluate a trait's influence on fitness in the context of moderate levels of natural selection and high levels of sexual selection.…”
Section: Introductionmentioning
confidence: 99%